HAKIKAT KEDUDUKAN DAN FUNGSI BAHASA INDONESIA DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA - Jahidin, Jahidin (Edukasi Kultura, 2024)
Language is a regular system of sound symbols used to express feelings and thoughts that are used by members of a society to work together, interact, and to communicate with other humans either through gestures, namely gestures, speech i.e. everyday speech. The purpose of this article is to explain the position of the nature of language and the philosophy of language taken from several expert opinions to further explain the material. Language development is an increase in the ability to master communication tools, both verbally, in writing and using sign signs. The relationship of philosophy to language, is a system of symbols that is not only an empirical sequence of sounds , it has a nonempirical meaning. In the development of its use, Indonesian has two kinds of functions, namely as a national language and an official state language. As a national language, Indonesian is used as a tool to unite the Indonesian nation. Meanwhile, as the official language of the state, Indonesian is a language used for government administration activities, especially for official activities.